An evaluation of microalgae as a recombinant protein oral delivery platform for fish using green fluorescent protein (GFP). Issue 87 (April 2019) - Kwon, Kwang-Chul; Lamb, Antonio; Fox, David; Porphy Jegathese, Simon Jegan
Abstract: Recombinant proteins produced by biological systems such as bacteria, yeasts, mammalian and insect cell cultures are widely used for clinical or industrial purposes. Most therapeutic protein drugs require purification, cold chain, and injection, which make them prohibitively expensive and hinders their widespread use. Here, we describe a new economical oral vaccination platform using algae and evaluated its potential for the delivery of recombinant drugs using GFP expressed in the chloroplast of algal cells. The transplastomic algae expressing recombinant GFPs were freeze-dried for long-term storage at ambient temperature and for easy handling in feeding. GFPs bioencapsulated by lyophilized Chlamydomonas reinhardtii were found intact without degradation for several months at ambient temperature. The expression level of GFP in the lyophilized algae was estimated at 0.47 μg/mg dry weight. The GFPs bioencapsulated and orally delivered to Danio rerio were immunostained and observed in the intestinal tissues using a confocal microscope. Furthermore, the uptaken GFPs in the intestine were detected in the blood using ELISA and the detected level was 5.4 ng of GFP/μl of serum. These results demonstrate that microalgae can be a viable protein production and oral delivery system to vaccinate fish. The results give greater justification to continue exploring the concept of microalgal-based oral vaccines. The potential of the technology would greatly benefit aquaculture farmers by providing them with affordable, environmentally sustainable, and user-friendly vaccines. Highlights: GFPs bioencapsulated by lyophilized Chlamydomonas reinhardtii are found intact. Orally delivered bioencapsulated GFPs were detected in zebrafish intestinal tissues. GFPs were further detected in the circulatory system of zebrafish.